2019
DOI: 10.1055/s-0039-1685214
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Associated with Connective Tissue Disease

Abstract: Pulmonary hypertension (PH) is common in most forms of connective tissue disease (CTD); the prevalent type of PH depends on the particular CTD. Thus, pulmonary arterial hypertension (PAH) is dominantly associated with scleroderma, while postcapillary PH is most common in rheumatoid arthritis and lung disease-associated PH is typically found in myositis and sarcoidosis.Considerable expertise is required to identify, diagnose, and manage CTD-PH, as the primary physicians providing the majority of care for this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 74 publications
(74 reference statements)
0
28
0
7
Order By: Relevance
“…The most common CTDs that present with group 3 PH-ILD are SSc, mixed CTD, sarcoidosis, and idiopathic inflammatory myositis. 4,9 The widespread variation in prevalence is because of the diagnostic techniques used to define PH and/or ILD. Furthermore, there are concomitant and multifactorial mechanisms leading to PH, and many of the studies diagnosed PH patients without RHC and through doppler echocar-…”
Section: Prevalence Of Ild and Ph-ild In Connective Tissue Diseases (World Health Organization Group 3 Ph)mentioning
confidence: 99%
See 3 more Smart Citations
“…The most common CTDs that present with group 3 PH-ILD are SSc, mixed CTD, sarcoidosis, and idiopathic inflammatory myositis. 4,9 The widespread variation in prevalence is because of the diagnostic techniques used to define PH and/or ILD. Furthermore, there are concomitant and multifactorial mechanisms leading to PH, and many of the studies diagnosed PH patients without RHC and through doppler echocar-…”
Section: Prevalence Of Ild and Ph-ild In Connective Tissue Diseases (World Health Organization Group 3 Ph)mentioning
confidence: 99%
“…In SSc patients, emphysema can occur regardless of smoking status. 3 Based on the results of the Framingham study, a PA ≥ 29 mm in males and ≥ 27 mm in females is considered to represent abnormal dilation. 36 This is not as sensitive in patients with ILD or CTD that have other reasons for dilated pulmonary arteries.…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8) The pathogenesis of PAH is highly complex, and both environmental and genetic pathogenic factors can impair pulmonary vascular structure and function, thus leading to PAH. 9) The well-established environmental risk factors encompass congenital heart disease (CHD), [10][11][12][13] valvular heart disease, 14,15) virus infection, 16,17) connective tissue disease, [18][19][20] chronic thromboembolism, [21][22][23][24] chronic obstructive pulmonary disease, 25) pulmonary tumor thrombotic microangiopathy, 26,27) intake of chemical drugs or toxins, [28][29][30][31] and long-term exposure to hypoxia. [32][33][34][35] However, emerging evidence has demonstrated that genetic defects play a pivotal role in the pathogenesis of idiopathic PAH, especially for familial PAH, and deleterious mutations in multiple genes, including BMPR2 encoding a receptor of the transforming growth factor-β superfamily, TBX4 encoding a transcription factor, and KCNK3 as well as ABCC8 encoding potassium channels, have been found to cause PAH.…”
mentioning
confidence: 99%